Novel dual superlyophobic cellulose membrane for multiple oil/water separation. (February 2020) - Li, Yubin; He, Yi; Fan, Yi; Shi, Heng; Wang, Yuqi; Ma, Jing; Li, Hongjie
Abstract: Materials with superwettability are promising for oil/water separation, yet the requirement for on demand separation of various types of oil/water system is still a challenge. In this work, we present that the polypyrrole-coated cellulose membrane was fabricated via in situ polymerization of pyrrole on a filter paper (PPy@FP) or a mixed cellulose acetate membrane (PPy@CA). The roughness of the PPy@FP membrane was controlled by adjusting the polymerization time, and corresponding morphology of the membrane was studied by scanning electron microscopy (SEM), which shows that the PPy@FP-50 membrane has nanoscale rough structure. Meanwhile, attenuated total reflections Fourier transform infrared spectrometer (ATR-FTIR), X-ray photoelectron spectrometer (XPS), and conductivity tests confirmed that polypyrrole was coated on the filter paper successfully. Contact angle tests displayed that the surface of modified membrane has dual superlyophobicity. The green and renewable cellulose and chemical stable polypyrrole endow this novel material with outstanding properties of chemical resistance to acid, mild alkali (pH = 1–11) and salty environment. Besides, the modified membranes also obtain high flux (over 3000 L∙ m −2 ∙h −1 for mixtures, over 1000 L∙ m −2 ∙h −1 for oil-in-water emulsions and over 100 L∙ m −2 ∙h −1 for water-in-oil emulsions) and good separation efficiency (around 99%)). Besides, it also shows good recyclability towards different oil/water system. Highlights: Polypyrrole-cellulose membranes were obtained via in situ polymerization of pyrrole on the filter paper and CA membrane. The surface of the modified membrane exhibits unusual dual superlyophobic wettability. The PPy@FP-50 membrane can realize selective separation of light/heavy oil-water mixture under gravity. The PPy@CA-50 membrane can separate both two types of emulsions at low applied pressure difference.